Autophagy: A Primer for the Gastroenterologist/Hepatologist - Christiane Sokollik; Michelle Ang; Nicola L Jones (Canadian Journal of Gastroenterology)
Autophagy is a conserved cellular pathway that maintains intracellular homeostasis by degrading proteins and cytosolic contents of eukaryotic cells. Autophagy clears misfolded and long-lived proteins, damaged organelles and invading microorganisms from cells, and provides nutrients and energy in response to exposure to cell stressors such as starvation. Defective autophagy has recently been linked to a diverse range of disease processes of relevance to gastroenterologists and hepatologists including Crohn’s disease, pancreatitis, hepatitis and cancer. The present article provides an overview of the autophagy pathway and discusses gastrointestinal disease processes in which alterations in autophagy have been implicated. The clinical significance of autophagy as a potential therapeutic option is also discussed.